Human archipelago - Cole, Teju 1975- (Steidl, 2018)
With Cole's words and Sheikh's photos of displaced humans, we are confronted with fundamental and newly necessary questions of coexistence: who is my neighbor? Who is kin to me? Who is a stranger? What does it mean to be human?
Keywords: Sheikh, Fazal -- 1965-; Landschaftsfotografie; Flüchtling; Porträtfotografie; Humanity; Humanity / Pictorial works; Refugees; Refugees / Pictorial works; Photography, Artistic; Refugees in art; Portrait photography; Pictorial works